Children's right to participation in Swedish child welfare – The extent, nature and determinants of child interviews during investigations - Pålsson, David; Leviner, Pernilla; Wiklund, Stefan (Child abuse & neglect, 2025)
Children's right to participation in child welfare decision-making is highlighted in law and research. However, there is a lack of comprehensive empirical research on how such participation is actually fulfilled. This article aims to describe and analyse the extent, nature and determinants of children's participation in child welfare investigations in Sweden as well as to discuss barriers to participation. The dataset comprises a cohort of 2123 children investigated during 2022 across eight municipalities in Stockholm County, Sweden. The study is based on cross-sectional data where the responsible child welfare workers served as informant in a survey focusing child and case factors concerning 2123 children subject to child welfare investigations. The data is analysed by using descriptive and binary logistic regression analyses. In approximately 75 % of the child welfare investigations, child welfare workers held interviews with the child (with or without parental presence) while individual child interviews were carried out in about 50 % of the cases. Multiple interviews (≥3) occurred in 14 % of the cases. Reasons for not interviewing children included finding interviews to be unnecessary, perceiving the child as too young, and reluctance by the child as to participation. Investigations involving older children and referrals related to abuse increased the odds for participation. The study suggests that more children are interviewed by child welfare authorities than found in previous studies, but that there still is a gap between the legislative intention to facilitate child participation and the actual state of child welfare practice.